(untitled) (International Journal of Atharva, 2025)
Background: This article critically examines the subversion of stereotypical gender roles in B.P. Koirala’s novel Hitler ra Yahudi, focusing on the characters Rewa, Mrs. Macdonald, and Yakub. Methods: Drawing upon Butler’s (2007) theory of gender performativity and Kaplan’s (2015) conceptualization of travel as a metaphor for identity renegotiation, the study explores how the characters’ physical and emotional journeys serve as catalysts for challenging and redefining orthodox gender norms. Findings: Applying the frameworks above, the paper infers that the protagonists’ experiences reflect the fluidity of gender identities and their capacity to dismantle entrenched stereotypes. However, the analysis also problematizes the extent to which these subversions are sustained within the narrative, considering the sociocultural constraints that may reassert traditional gender roles. Conclusion: Ultimately, this study concludes that while journeys in Hitler ra Yahudi provide a platform for reconstructing gender identities, the persistence of normative structures complicates the realization of lasting transformation. Novelty: Travel helps blur the deep-rooted stereotypical gender roles in society by exposing individuals to multiple roles they can play during the journey. Therefore, travel is the means to subvert the stereotypical gender roles.